Contrasting strategies for wing‐moult and pre‐migratory fuelling in western and eastern populations of Common Whitethroat Sylvia communis. (7th November 2018) - Remisiewicz, Magdalena; Bernitz, Zephné; Bernitz, Herman; Burman, Marc S.; Raijmakers, Jacobus M.H.; Raijmakers, Johannes H.F.A.; Underhill, Les G.; Rostkowska, Anna; Barshep, Yahkat; Soloviev, Sergej A.; Siwek, Ilona
Abstract : Trade‐offs between moult and fuelling in migrant birds vary with migration distance and the environmental conditions they encounter. We compared wing moult and fuelling at the northern and southern ends of migration in two populations of adult Common Whitethroats Sylvia communis . The western population moults most remiges at the breeding grounds in Europe (e.g. Poland) and migrates 4000–5000 km to western Africa (e.g. Nigeria). The eastern population moults all remiges at the non‐breeding grounds and migrates 7000–10 000 km from western Asia (e.g. southwestern Siberia) to eastern and southern Africa. We tested the hypotheses that: (1) Whitethroats moult their wing feathers slowly in South Africa, where they face fewer time constraints than in Poland, and (2) fuelling is slower when it coincides with moulting (Poland, South Africa) than when it occurs alone (Siberia, Nigeria). We estimated moult timing of primaries, secondaries and tertials from moult records of Polish and South African Whitethroats ringed in 1987–2017 and determined fuelling patterns from the body mass of Whitethroats ringed in all four regions. The western population moulted wing feathers in Poland over 55 days (2 July–26 August) at a varying rate, up to 13 feathers simultaneously, but fuelled slowly until departure in August–mid‐September. In Nigeria, during the drier period of mid‐February–March they fuelled slowly, but the fuelling rate increased three‐fold in April–May after the rains before mid‐April–May departure. The eastern population did not moult in Siberia but fuelled three times faster before mid‐July–early August departure than did the western birds moulting in Poland. In South Africa, the Whitethroats moulted over 57 days (2 January–28 February) at a constant rate of up to nine feathers simultaneously and fuelled slowly from mid‐December until mid‐April–May departure. These results suggest the two populations use contrasting strategies to capitalize on food supplies before departure from breeding and non‐breeding grounds.